Refractive index to evaluate staining specificity of extracellular vesicles by flow cytometry - de Rond, L.; Libregts, S.F.W.M.; Rikkert, L.G.; Hau, C.M.; van der Pol, E.; Nieuwland, R.; van Leeuwen, T.G.; Coumans, F.A.W. (Journal of extracellular vesicles, 2019)
Extracellular vesicles (EVs) in plasma are commonly identified by staining with antibodies and generic dyes, but the specificity of antibodies and dyes to stain EVs is often unknown. Previously, we showed that platelet-depleted platelet concentrate contains two populations of particles >200 nm, one population with a refractive index (RI) < 1.42 that included the majority of EVs, and a second population with an RI > 1.42, which was thought to include lipoproteins. In this study, we investigated whether EVs can be distinguished from lipoproteins by the RI and whether the RI can be used to determine the specificity of antibodies and generic dyes used to stain plasma EVs. EVs and lipoproteins present in platelet-depleted platelet concentrate were separated by density gradient centrifugation. The density fractions were analyzed by Western blot and transmission electron microscopy, the RI of particles was determined by Flow-SR. The RI was used to evaluate the staining specificity of an antibody against platelet glycoprotein IIIa (CD61) and the commonly used generic dyes calcein AM, calcein violet, di-8-ANEPPS, and lactadherin in plasma. After density gradient centrifugation, EV-enriched fractions (1.12 to 1.07 g/mL) contained the highest concentration of particles with an RI < 1.42, and the lipoprotein-enriched fractions (1.04 to 1.03 g/mL) contained the highest concentration of particles with an RI > 1.42. Application of the RI showed that CD61-APC had the highest staining specificity for EVs, followed by lactadherin and calcein violet. Di-8-ANEPPS stained mainly lipoproteins and calcein AM stained neither lipoproteins nor EVs. Taken together, the RI can be used to distinguish EVs and lipoproteins, and thus allows evaluation of the specificity of antibodies and generic dyes to stain EVs.